The effect of the structure of gasses on the quality indicators (Texas Journal of Engineering and Technology, 2022)
In this article, the structure of yarns is studied from a theoretical point of view, and the effect of yarn quality parameters on yarns and yarns is analyzed. The results obtained on the basis of research were theoretically analyzed and appropriate conclusions were drawn.